Elite letrada e ofício docente em Sergipe no século XIX - Santos, Fabio Alves dos (2013)
This research had as invest igat ive focus the relationship between the work of teaching and the literate elite in Brazil in the 19th century, from the case of the province of Sergipe d´El Rey. The main objective was to identify and an alyze the place occupied by teaching during the groups (mentioned above) life trajectories. The data base was built having as source the Dicionário Biobibliográfico Sergipano, written by Manoel Armindo Cordeiro Guaraná. From this document, it was possible to draw up a prosopographic study, sustained by the concepts of field, capital and habitus elaborated by Pierre Bourdieu. The hypothesis that guided this research consisted in understanding that throughout the 19th century the work of teaching, in its different types, was an important field of activity of the literate elite and this activity contributed to the sett ing of teaching as a profession in a decisive manner. Trying to understand the profession of teaching only through actions aimed at primary school teachers, or the presence of women, does not seem to be sufficient for a further look into the issue. This assertion, though obvious, needs to be repeated taking into account what is recurrent in academic literature on the profession of teaching. It has repeatedly taken the morphological characteristics belonging to teaching as something given and natural and not as the result of the sociohistorical game of power relationships between groups that are vying for the educational field. The study on the relationship between the literate elite and teaching reveals that it is a mistake to think of teaching as a monolithic block, a homogeneous whole, as it has been recur rent in the Brazilian education historiography. It is clear that it is more fruitful thinking of ´teachers´, ´professors´ in a more pluralistic perspective. If the organization of primary teachers constitutes a fundamental element for the consolidation of teaching as a profession, we cannot deny either that the acting of a literate elite in this sense had great relevance.